Visual Analysis of Pelo Dalang Animation - S I P Persada (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
When viewed from the objective of the study, it is to find out the relationship of each dimension of the character that appears in the animation of the dalang pelo so that it can be obtained whether the physical appearance of the character in the animation of the dalang pelo is in accordance with the sociology and psychology of the character, so that the results can be obtained whether the visual of this character suitable with the nature of this character itself where from this research it was concluded that the characters in the animation of the dalang Pelo are partly appropriate when viewed from Physiological Dimensions, Sociological Dimensions, Psychological Dimensions where the benefit of this research is to provide a reference to design practitioners in making character where in making a character one must think about the suitability of Physiological Dimensions, Sociological Dimensions, Psychological Dimensions so that only by looking at the physical character of the character we can know the nature and habits of the character as well as adding to the rules of Science in the Field of Design. ain so that this research can be used as a reference for academics to make research, especially dissecting characters in a design work.